(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
A 15 × 20 × 1.6 mm3 a novel T shape patch Antenna inspired by unit cell is investigated by changing position of meta cell. The proposed antennas have dual band (3.53-5.3GHz) and tri band (3.1-3.2GHz, 4.9- 5.56GHz, 6.22-6.76GHz) nature operating at S, C band Applications .Here we observed the designed antenna has S11 < −10 dB and gain was positive at operating bands.